2023
DOI: 10.1111/cns.14287
|View full text |Cite
|
Sign up to set email alerts
|

rTMS ameliorates depressive‐like behaviors and regulates the gut microbiome and medium‐ and long‐chain fatty acids in mice exposed to chronic unpredictable mild stress

Abstract: IntroductionRepetitive transcranial magnetic stimulation (rTMS) is a clinically useful therapy for depression. However, the effects of rTMS on the metabolism of fatty acids (FAs) and the composition of gut microbiota in depression are not well established.MethodsMice received rTMS (15 Hz, 1.26 T) for seven consecutive days after exposure to chronic unpredictable mild stress (CUMS). The subsequent depressive‐like behaviors, the composition of gut microbiota of stool samples, as well as medium‐ and long‐chain fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…At the same time, the brain has the capacity to regulate the gastrointestinal tract and the enteric nervous system, thereby exerting an influence on the composition of the gut microbiota ( Rhee et al, 2009 ). In this context, neuroregulatory techniques like repetitive transcranial magnetic stimulation (rTMS) ( Zhou et al, 2023 ), vagus nerve stimulation (VNS) ( Campbell et al, 2016 ) and transcranial direct current stimulation (tDCS) ( Artifon et al, 2020 ) have been reported to affect the gut microbiota. Similarly, EA could also influence the composition and activity of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the brain has the capacity to regulate the gastrointestinal tract and the enteric nervous system, thereby exerting an influence on the composition of the gut microbiota ( Rhee et al, 2009 ). In this context, neuroregulatory techniques like repetitive transcranial magnetic stimulation (rTMS) ( Zhou et al, 2023 ), vagus nerve stimulation (VNS) ( Campbell et al, 2016 ) and transcranial direct current stimulation (tDCS) ( Artifon et al, 2020 ) have been reported to affect the gut microbiota. Similarly, EA could also influence the composition and activity of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The OFT was performed according to a recent study ( 49 ). The mice were placed in the center of an open-field box (40 cm × 40 cm × 40 cm), and then the activity was recorded for a period of 5 min.…”
Section: Methodsmentioning
confidence: 99%